Effects of dietary fiber and threonine on performance, intestinal morphology and immune responses in broiler chickens - Saadatmand, Nasim (Anim Nutr, 2019)
The present experiment was conducted to investigate the effects of fiber and threonine (Thr) on growth performance, intestinal morphology and immune responses of broiler chickens. A total of 420 one-day-old mixed sex broiler chicks (Ross 308) were randomly divided into 6 experimental diets and 5 replicates of 14 chicks based on a factorial arrangement (2 × 3) from 1 to 42 d of age. Experimental factors included dietary supplemental fiber type (no supplemental fiber [NSF], 30 g/kg sugar beet pulp [SBP] or 30 g/kg rice hull [RH]) and Thr inclusion level (100% or 110% of Thr requirement recommended by breeder company [Ross 308]). Growth performance of broilers was assayed at different periods of the experiment. Intestinal morphometric features were measured at 21 d of age. Antibody titer against sheep red blood cells (SRBC), Newcastle and influenza disease viruses were measured on d 30 of trial. Dietary inclusion of SBP and RH significantly decreased feed intake and weight gain during the entire rearing period (P < 0.05). Interaction of fiber and Thr had no beneficial effects on the performance of chickens across the entire rearing phase. Dietary supplementation of 110% Thr required level improved jejunal morphometric features (P < 0.05), whereas its inclusion with fibrous materials failed to show the same effects. Dietary supplemental Thr together with SBP significantly increased antibody production against SRBC (P < 0.05). In conclusion, although supplemental 30 g/kg fibrous materials impaired growth performance, inclusion of SBP along with 110% Thr level improved the humoral immunity in broiler chickens.